Analisa Performa Internet Satelit Leo (Starlink) Dalam Kondisi Variasi Cuaca Di Sembalun, Lombok Timur, Nusa Tenggara Barat - I Nyoman Dimas Bayu Semara Putra; Made Sutha Yadnya; Muhamad Syamsu Iqbal (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2026)
Internet access has become an essential requirement across various sectors, including healthcare, education, government services, and economic activities. However, internet distribution in Indonesia remains uneven, particularly in areas with extreme geographical conditions, such as the mountainous region of Sembalun, East Lombok. Topographical barriers make the development of conventional terrestrial network infrastructure difficult, costly, and less efficient. Low Earth Orbit (LEO) satellite internet technology, such as Starlink, offers an alternative connectivity solution because it can provide internet access without relying entirely on ground-based infrastructure. This study aims to analyze the performance of Starlink internet service in Sembalun based on Quality of Service (QoS) parameters, including throughput, latency, jitter, and connection stability. This research employed an experimental method through field data collection at Sembalun Public Health Center using a Starlink satellite modem and Wireshark application. Measurements were conducted under various weather conditions to obtain a more comprehensive overview of service performance. The findings of this study are expected to provide empirical information regarding the effectiveness of Starlink as a connectivity solution in mountainous areas and serve as a reference for the utilization of LEO satellite internet technology in remote regions or areas with similar geographical characteristics.